2018
DOI: 10.1002/adhm.201801054
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Gelatin Methacryloyl Microneedles for Transdermal Drug Delivery

Abstract: Biocompatible and bioresponsive microneedles (MNs) are emerging technology platforms for sustained drug release with a potential to be a key player in transdermal delivery of therapeutics. In this paper, an innovative biodegradable MNs patch for the sustained delivery of drugs using a polymer patch, which can adjust delivery rates based on its crosslinking degree, is reported. Gelatin methacryloyl (GelMA) is used as the base for engineering biodegradable MNs. The anticancer drug doxorubicin (DOX) is loaded int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
139
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 218 publications
(140 citation statements)
references
References 44 publications
1
139
0
Order By: Relevance
“…The mechanical properties of the patches were measured by a low‐force mechanical testing system (5943 MicroTester, Instron, USA) according to the related work 29,42,58. Briefly, The patch was placed needle‐side up on a stainless‐steel plate and compressed with a load cell at a rate of 1 mm min −1 up to the maximum loading force of 50 N. Correlations between the applied force and deformation of the patch were recorded during the whole testing process.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanical properties of the patches were measured by a low‐force mechanical testing system (5943 MicroTester, Instron, USA) according to the related work 29,42,58. Briefly, The patch was placed needle‐side up on a stainless‐steel plate and compressed with a load cell at a rate of 1 mm min −1 up to the maximum loading force of 50 N. Correlations between the applied force and deformation of the patch were recorded during the whole testing process.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we have demonstrated that gelatin methacryloyl (GelMA) is a suitable material for the fabrication of MNs as it has good biocompatibility and desirable drug delivery properties 29. The nature‐derived GelMA MN patch possesses good biocompatibility as a medical device for sourcing ISF in a convenient and minimally invasive manner.…”
Section: Figurementioning
confidence: 99%
“…Dissolving MNs are mainly used in drug delivery [100]. They are usually fabricated with biodegradable polymer or sugar, which endows the MNs with bio-acceptability and good patient compliance [101,102]. The tips of MNs can detach from the substrate of MNs upon contact with skin interstitial fluid.…”
Section: Dissolving Mnsmentioning
confidence: 99%
“…3B). GelMA had been reported to have a MMPs-responsive property (38). Thus, we evaluated the ability of the G/Mino + Vor hydrogel to release the encapsulated minocycline and vorinostat in response to MMPs in vitro (Fig.…”
Section: Preparation Of Mmps Responsive G/mino + Vor Hydrogel For Locmentioning
confidence: 99%